Adoption and performance of better cotton management practices in Pakistan - Zulfiqar, Farhad; Thapa, Gopal B.; Soparth Pongquan; Datta, Avishek; Higher Education Commission (HEC), Pakistan; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
In view of adverse socioeconomic and environmental effects of conventional cotton, 2better cotton3 was introduced by the Better Cotton Initiative (BCI) in Pakistan in 2009. There is a dearth of research on level of adoption of 2better cotton3 production practices as recommended by BCI, financial attractiveness of 2better cotton3 as compared to conventional cotton and potential for further improvements in 2better cotton3 based on resource use efficiency analysis. This research was carried out to bridge these gaps. The field survey, covering 161 2better cotton3 farmers and 141 conventional farmers, was carried out in Punjab province of Pakistan.The level of adoption of 2better cotton3 practices was examined based on actual number of practices used by farmers, and its determinants were analyzed by the help of truncatedregression. The financial analysis involved the comparison of conventional and 2better cotton3 using net profit and benefit cost ratio measures. The net income was analyzed using propensity score matching method to ensure that the income was attributed to 2better cotton3 production rather than other external factors. Technical, allocative and economic efficiency of 2better cotton3 were analyzed using input orienteddata envelopment analysis method. Factors affecting technical and economic efficiency were identified using bootstrapped truncated regression. Results of the analysis of the level of adoption of 2better cotton3 practices involving land preparation and sowing, crop management, and picking and post-harvestpractices displayed clear variations. The only significant factor positively affecting the adoption across the three practice groups was information access from formal sources.This indicates that the knowledge and training provided by formal organizations had played a significant role in the use of 2better3 practices. Financially, returns from 2better cotton3 were far better than conventional cotton primarily because of the lower input cost attributed to mainly the significantly low cost of irrigation, chemical fertilizers and pesticides. 2Better cotton3 was also socially and environmentally better than conventional cotton due to application of relatively smaller amounts of inorganic pesticides and herbicidesand higher amounts of organic fertilizers. There was a variation in technical efficiency and it was positively influenced by farmers{u2019} education, farming experience, and drainage status, while it was negatively influenced by the number of household members involved in farming, and the area under cotton. The mean economic efficiency of 56 percent indicated that at the current productivity level inefficient farmers can reduce their costs by 44 percent. The economic efficiency was negatively affected by the number of household members involved in farming and intensity of use of crop management practices. Policy recommendations are made to promote the production of 2better cotton3 in other parts of Pakistan by focusing on knowledge dissemination, training and regular interaction with farmers. Efforts should also be made to improve input use efficiency of particularly those 2better cotton3 farmers who are currently operating inefficiently.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Regional and Rural Development Planning
Thesis (Ph. D.) - Asian Institute of Technology, 2016
Keywords: Cotton -- Pakistan -- Management